Β-Blocker treatment during pregnancy and adverse pregnancy outcomes: a nationwide population-based cohort study. Issue 4 (19th July 2012) - Meidahl Petersen, Kasper; Jimenez-Solem, Espen; Andersen, Jon Traerup; Petersen, Morten; Brødbæk, Kasper; Køber, Lars; Torp-Pedersen, Christian; Poulsen, Henrik Enghusen
Abstract : Objective: To investigate the association between exposure to β-blockers during pregnancy and the risk of being born small for gestational age (SGA), preterm birth and perinatal mortality in a nationwide cohort. Design: A population-based retrospective cohort study, using the Danish Fertility Database. The authors identified all pregnant women redeeming a prescription for β-blockers using the National Prescription Registry. Multivariate logistic regression models were used to assess the association between exposure and our outcomes. Setting: Register-based survey. Participants: 911'685 births between 1995 and 2008 obtained from the Danish Fertility Database. Outcome measures: Being born SGA was defined as having a birth weight below the 10th percentile for the corresponding gestational week. Preterm birth was defined as birth before the 37th gestational week. Perinatal mortality was defined as either death occurring within the first 28 days of life or stillbirth. Before 2004, fetal deaths were recorded as stillbirths if they occurred after 28 weeks of gestation, but since then stillbirth is recorded for deaths after 22 gestational weeks. Results: The authors identified 2459 pregnancies exposed to β-blockers. β-Blocker exposure during pregnancy was found to be associated with increased risk of SGA (adjusted OR 1.97, 95% CI 1.75 to 2.23), preterm birth (adjusted OR 2.26, 95% CI 2.03 to 2.52) and perinatal mortality (adjusted OR 1.89, 95% CI 1.25 to 2.84). Analyses were adjusted for socioeconomic and maternal variables. The authors found similar risk profiles for pregnancies exposed to labetalol and for pregnancies exposed to other β-blockers. Conclusions: The authors found that exposure to β-blockers during pregnancy was associated with being born SGA, preterm birth and perinatal mortality. Our findings show that labetalol is not safer than other β-blockers during pregnancy.